Akses Jaminan Kesehatan terhadap Pekerja Perempuan Rentang Umur 25-29 Tahun pada Setiap Provinsi di Indonesia Tahun 2017: Studi Cross-Sectional - Dewi, Rahma Rosita; Fatonah, Sabrina Putri; Amalia, Zahra; Mahmud, Intan Silmi Alya; Ramadhan, Rayhan (UI Scholars Hub, 2025)
Health insurance is a fundamental right guaranteed by the Indonesian government. However, coverage among female workers aged 25–29 remains low with significant disparities across regions. This cross-sectional study aims to analyze access to health insurance among female workers aged 25–29 in Indonesia and identify factors contributing to these gaps. The study used secondary data from the 2017 Indonesian Demographic and Health Survey (SDKI), involving 8,394 women who met the inclusion criteria, focusing on health insurance ownership status. Descriptive analysis was conducted to assess the distribution of coverage proportions across regions, with bias control performed through data selection and multi-layered validation of the 2017 IDHS data. The main variables included health insurance ownership and respondents' age. Among all respondents, only 30.50% had health insurance, while 69.50% lacked coverage. Higher coverage rates were observed in Aceh, West Java, and West Sulawesi. This study highlights the urgent need for more equitable health insurance distribution particularly in areas with limited access to healthcare coverage. Strengthening healthcare infrastructure, reinforcing health insurance policies, increasing public awareness, and optimizing the National Health Insurance Program (JKN) are essential steps to achieving comprehensive coverage.